Explaining Youth Online Disaster Risk Information Seeking In Disaster-Prone Areas: A Case of an Indonesian Coastal Community - Amelia Putri; Dicky Chresthover Pelupessy (Green Publisher Indonesia, 2025)
This study tested the utility of the Risk Information Seeking and Processing (RISP) model in explaining disaster risk information-seeking intentions among rural youth in Indonesia. Participants (N = 98) completed a survey measuring RISP constructs, including information insufficiency, perceived hazard characteristics, affective response, informational subjective norms, perceived information gathering capacity, and behavioral beliefs. Regression analysis showed that perceived hazard characteristics (β = 0.114, p < .05) and informational subjective norms (β = 0.344, p < .001) were significant predictors of information-seeking intention, while affective response and behavioral beliefs were not significant (p > .05). The RISP model explained 23.6% of the variance in information-seeking intention (R² = 0.236, Adjusted R² = 0.203). Adding gender as a random effect slightly improved model fit (Conditional R² = 0.267), but gender accounted for minimal variance. These findings extend the RISP model to a high-risk, underrepresented population and provide important theoretical and practical insights for designing targeted risk communication strategies to enhance disaster preparedness among youth.